Production of a confused sea in a rectangular model basin - Glover, Robert E. (Robert Ellsworth), 1896-1984, author; Colorado A and M College, Department of Civil Engineering, publisher (Colorado State University. Libraries, 1957)
An arrangement of three cam controlled wave generators ls described for producing a sea of the confused type ln a model basin in which random wave amplitudes, wave lengths and orientation of propagation directions are possible.
CER57REG-23.
March 1957.
Prepared for David Taylor Model Basin.
Technical report no. 4.
Keywords: Ocean waves -- Simulation methods